Addressing gender in climate information production and communication in West Africa: are we on track? - Ali, Abdou; Gadédjisso-Tossou, Agossou; Agali, Alhassane; Mohamed, Hamatan; Segnon, Alcade C; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
West African women, youth and marginalized people are particularly exposed to the adverse effects of climate change and variability, because of their very limited access to climate services and informations. These disadvantaged people must be extensively involved in training and capacity building on understanding climate risks and response options to cope with these hazards. It is imperative to mainstream the opinions of women, youth and marginalized people in the production, dissemination, communication and use of climate services and information in West Africa